Prevalence and Histopathological Findings of Endometrioid Carcinoma and Associated Risk Factors: A Cross-Sectional Study: Prevalence and Histopathology of Endometrioid Carcinoma - Pervez, Shagufta Nasir; Junaid, Muhammad; Alam, Shaista; Baloch, Farhan Abbas; Khan, Pordil; Bibi, Noushad (Pakistan Journal of Health Sciences, 2024)
Ovarian cancer ranks as the seventh most frequently diagnosed malignancy among women worldwide. Endometrioid carcinoma, a type of proliferative endometrial tumor, accounts for approximately 15% of epithelial ovarian cancers, making it the third most common subtype. Objective: To investigate the relationship between Endometrioid Carcinoma and potential risk factors, including demographic, reproductive, and lifestyle factors. Methods: A cross-sectional study was conducted at Hayatabad Medical Complex’s Department of Pathology from January 1 to December 31, 2023. The study analyzed 139 ovarian tumor specimens confirmed through histopathology. Statistical analysis using SPSS version 26 identified significant associations between variables using Chi-square tests and logistic regression, with a significance level of p < 0.05. Results: A total of 139 ovarian specimens with the patient’s mean age (45.34 years) with the highest prevalence of endometrioid carcinoma observed in women aged 40-49 and 60 years and above. The prevalence of endometrioid carcinoma was about 14.4% (n=20). A significant association was identified between parity and endometrioid carcinoma (p-value = <0.001). Menopausal status also showed a significant association, with postmenopausal women having a higher prevalence of endometrioid carcinoma. Logistic regression analysis indicated that age was a significant predictor of endometrioid carcinoma (p-value = 0.028). Conclusions: Significant association between nullipara and premenopausal women with endometrioid carcinoma, emphasizing the importance of considering parity and menopausal status as a risk factor for endometrioid carcinoma.